Ritual and archaic states (University Press of Florida, 2017)
Ritual and archaic states frequently ignite complex debates about their defining characteristics and archaeological signatures. Offering fresh perspectives on both subjects, this volume unites the two streams of scholarship and explores the varying nature, expression, and significance of ritual in archaic states. It compares rituals across many different archaic polities and cultures, including Vijayanagara, Swahili Lamu, Venice, Asante, Aztec, Ming China, Oaxaca, Greece, Inca, Wari, and Chaco.